A Model for the Dispersion of the Migrant Labor Force and Some Results for the United States, 1880-1920 - Orsagh, Thomas J.; Mooney, Peter J. (The Review of Economics and Statistics, 1970)
T HE geographical distribution and mobility of the labor force have received considerable attention in the literature. However, while various factors have been proposed to explain these phenomena, a satisfactory formal theory of the migration and subsequent location of the labor force, susceptible to empirical verification, has not yet evolved. With this study, we hope to contribute to this evolution by developing and empirically testing a more refined theoretical model through the use of a rich but seldom exploited body of statistical data. One dominant emphasis in the existing literature is on the wage or income differential thesis. Raimon [1], in an analysis of the patterns of interstate migration in the United States from 1950 to 1958, found significant rank correlations between percentage changes in population arising from migration and (1) levels of average per capita income (r = .75), and (2) average earnings of employed workers (r = .85). His results are supported by Gallaway, Gilbert and Smith [21], who in a study of interstate migration for a later period, suggest that income differentials are statistically significant in explaining interstate migratory patterns over the interval 1955-1960. On the other hand, Nelson's study [31] of interstate migration during the periods 1935-1940 and 1949-1950 shows no relationship between migration and income differentials; and Easterlin's European emigration study [4] concludes that per capita income, used by itself, was a poor predictor of migration rates. Finally, Fleischer's analysis [51] of postwar Puerto Rican migration to the United States shows that the ratio of gross hourly earnings in the source and receiving areas was, by itself, a very poor predictor. A second emphasis in the literature concerns what one might loosely call the job vacancy thesis. Except for Nelson, there is general agreement about the importance of this variable, whether it is expressed in terms of percentage changes in employment over states (Raimon), unemployment differentials (Gallaway, et al.), the ratio of unemployment levels in source and receiving areas (Fleischer), or cycles in economic activity (Easterlin). Along similar lines, Bjork [6] introduced an index of demand for migrant labor 1 based on the belief that the economic growth of the United States during the period 1880-1950 was accompanied by a dramatic differential growth in demand for agricultural as opposed to nonagricultural labor and by differential rates of natural increase of the population over states. Although their evidence is circumstantial and indirect, both Nelson and Fleischer hypothesize that the role of information afforded by the presence of friends and relatives is a significant variable affecting the magnitude of migratory movements. This opinion is shared by Kirk and Huyck [7], who assert that, . . in the choice of alternative overseas destinations the emigrant will almost always forego theoretical maximum opportunity for the practical advantages of locating among relatives, friends, and countrymen overseas. The interpretation of the results recorded above is rendered difficult not only because of differing definitions of the variables, but also because of the identification problem implicit in some of the models. We contend that the apparently contradictory findings with respect